A world history of photography - Rosenblum, Naomi (New York : Abbeville Press Publishers, 2007)
"A World History of Photography encompasses the entire range of the medium, from the camera lucida to the latest computer technology, and from Europe and the Americas to the Far East. It investigates all aspects of photography - aesthetic, documentary, commercial, and technical - while placing it in historical context. Included among the more than 800 photographs by men and women are both little-known and celebrated masterpieces, arranged in stimulating juxtapositions that illuminate their visual power." "Dr. Rosenblum's chronicle of photography is authoritative and unbiased, tracing both chronologically and thematically the evolution of this young art. Exploring the diverse roles that photography has played in the communication of ideas, Dr. Rosenblum devotes special attention to topics such as portraiture, documentation, advertising, and photojournalism, and to the camera as a medium of personal artistic expression. Profiles are provided of individual photographers who made notable contributions to the medium or epitomized a certain style."--Jacket.
The early years : technology, vision, users 1839-1875 -- A plenitude of portraits 1839-1890 -- The galerie contemporaine--appearance and character in 19th-century portraiture -- Documentation : landscape and architecture 1839-1890 -- The Western landscape--natural and fabricated -- Documentation : objects and events 1839-1890 -- A short technical history : part I -- A 19th-century forerunner of photojournalism--the execution of the Lincoln conspirators -- Photography and art : the first phase 1839-1890 -- New technology, new vision, new users 1875-1925 -- The origins of color in camera images -- Art photography : another aspect 1890-1920 -- Documentation : the social scene to 1945 -- Illuminating injustice : the camera and social issues -- Art, photography, and modernism 1920-1945 -- A short technical history : part II -- The machine : icons of the industrial ethos -- Words and pictures : photographs in print media 1920-1980 -- Photography since 1950 : the straight image -- Photography since 1950 : manipulations and color -- A short technical history : part III.
Includes bibliographical references (pages 666-683) and index.
Keywords: Photography -- History; Photography / History